1998
DOI: 10.1093/bioinformatics/14.10.846
|View full text |Cite
|
Sign up to set email alerts
|

Hidden Markov models for detecting remote protein homologies.

Abstract: karplus@cse.ucsc.edu; http://www.cse.ucsc.edu/karplus

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
674
0
3

Year Published

1999
1999
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 1,011 publications
(685 citation statements)
references
References 0 publications
8
674
0
3
Order By: Relevance
“…7 The generative models were trained from an existing library of SAM-T99 HMMs. The SAM-T99 algorithm, described more fully in Karplus et al, 9 builds an HMM for a SCOP domain sequence by searching the nonredundant protein database Swissprot for a set of potential homologs of the sequence and then iteratively selecting positive training sequences from among these potential homologs and refining a model. The resulting model is stored as an alignment of the domain sequence and final set of homologs.…”
Section: Results and Discussion Setup Of Competing Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…7 The generative models were trained from an existing library of SAM-T99 HMMs. The SAM-T99 algorithm, described more fully in Karplus et al, 9 builds an HMM for a SCOP domain sequence by searching the nonredundant protein database Swissprot for a set of potential homologs of the sequence and then iteratively selecting positive training sequences from among these potential homologs and refining a model. The resulting model is stored as an alignment of the domain sequence and final set of homologs.…”
Section: Results and Discussion Setup Of Competing Methodsmentioning
confidence: 99%
“…In order to identify remote homologs, methods such as profiles for protein families, 5 hidden Markov models (HMMs), 6,7 and iterative methods such as PSI-BLAST 8 and SAM 9 have been introduced. The basic idea behind these methods is to generate a representative model for each protein family.…”
Section: Introductionmentioning
confidence: 99%
“…The last stage is consisted of generative classification algorithm and discriminative classification algorithm. pHMMs software that are HMMER [38]and SAM [39] are used as the generative classsifier while SVMs software that are SVM-Struct [40] and SVM-Fold [41] are used as discriminative classification algorithm. Even though a similar approach has been conducted by Bernardes et al [42] in their work by comparing the performance of various multiple alignment software, yet they only use pHMMs for classification.…”
Section: Framework For Finding the Optimal Mesh Algorithmmentioning
confidence: 99%
“…Then, the multiple alignments are converted to .cn3 files using fa2cd (ftp://ftp.ncbi.nih.gov/pub/REFINER/). The multiple alignments have to be converted in such a way because the refinement algorithm only understand inputs in the form of CD format, that is the same format used by CDD [39] database. One or more iterations of refinement which contains a stage of 'block shifting' followed by a 'block editing' stage are performed in the algorithm.…”
Section: Refinement Algorithmmentioning
confidence: 99%
“…We therefore used these genes as seed sequences in more exhaustive searches. Initially, using the SAM-T99 search method described in www.cse.ucse.edu/research/compbio web page that uses a hidden Markov model [20], we found no homologies to T4denV in six different The score represents the number of false positives expected by chance. In this search the resulting matches are due to the presence of common helicase motifs and do not necessarily indicate that the genes identified have functions corresponding to the XP genes.…”
Section: Do We Know All Possible Strategies For Ner In All Organisms?mentioning
confidence: 99%